BankBuddy.ai—Business Expansion and Marketing Dilemma: A Case Study to Discuss the Ansoff Growth Matrix Concepts Combined with Business Expansion Strategies for Expanding into Emerging Markets. Issue 1 (June 2020) - Chintalapati, Srikrishna
Five more days to go until the new year, it was a warm, pleasant and busy morning in Dubai, United Arab Emirates. As the clock ticked 10 times, Aditya Bhagat (Aditya), a young, ambitious, passionate entrepreneur, is seemingly intrigued and curious. Exactly 30 minutes from now, he is scheduled to meet Surya Prasad (Surya), his friend, counterpart and co-founder of BankBuddy (www.bankbuddy.ai ). Half the office is already empty as most of the associates had left for the year-end holidays, Aditya wanted to use this time to carefully brainstorm, methodically plan and articulate his business strategies and get them ready for execution in the new year. Marketing strategy is of particular importance, arguably the most critical and complex element that also needs the most attention in the overall exercise. He clearly understands that their current business strategy of being headquartered in Dubai and staying focused on artificial intelligence 1 (AI) powered solutions for the banking industry has paid off so well in their current geographical focus—Middle Eastern and African countries. The time now to look at next wave of business expansion. This inadvertently raises the decision dilemma of choosing the most productive and promising growth path—where and what to expand? Should they expand into more geographies? Or should they diversify the product line and add more offerings? In which country and city should they set up the new base (centroid) and which countries do they target for expansion? Which are the other promising products/offerings they should be adding to their existing lines of business? Aditya knows that today is the time to address the 'elephant in the room'—where to invest my marketing money?